Enhancing Health Resilience through the Integration of Mindful Practices and Cultural Dimensions - Adeeniyan, Abbiodun; Ifeoma, Chioma; Amara, Eniola (Journal of Asian-african Focus in Health, 2024)
Health resilience is a critical determinant of communities' ability to adapt to and overcome health challenges, particularly in contexts with significant socio-economic and healthcare disparities, such as Nigeria. This qualitative study explored the potential of mindful practices and cultural integration to enhance health resilience within Nigerian communities. Using purposive sampling, 30 participants, including healthcare professionals, cultural leaders, and community health workers, were selected from diverse regions of Nigeria. Data were collected through semi-structured interviews and focus group discussions and analyzed using thematic analysis. The findings highlight the positive impact of mindfulness on emotional well-being and stress management, revealing its potential to improve health outcomes when adapted to align with local traditions. Culturally embedded health practices were found to play a pivotal role in shaping health behaviors, fostering community acceptance, and strengthening resilience. However, barriers such as limited awareness, resistance to change, and insufficient policy support hinder the widespread adoption of these integrated approaches. This study addresses gaps in existing literature by offering actionable insights for designing context-specific health interventions that leverage both modern psychological tools and traditional cultural practices. The integration of mindful practices and cultural dimensions presents an innovative pathway to address Nigeria's healthcare challenges, aligning with global health goals and fostering sustainable, culturally sensitive healthcare models. Future research should focus on evaluating the long-term impacts of such interventions and their scalability across diverse communities